Speech Acts In Newspapers of Cable News Network - Rohbiah, Tatu Siti; Al-Fariatunnisa, Anggun; Sa’dia, Siti (Humanus, 2022)
This research discussed about the analysis of speech acts in newspapers by the Cable News Network (CNN). The aim of this research is identifying the locutionary, illocutionary, and perlocutionary acts in newspapers of the Cable News Network (CNN). This research revealed the types and dominant types of speech acts that are found in newspapers. The method used in collecting data is qualitative descriptive. This research used some steps to be collected: reading the newspapers, identifying the newspapers, and classifying them into categories of speech acts. As a result, it was found that there were 117 utterances of speech acts in newspapers of the Cable News Network (CNN). They are 54 locutionary acts, 55 illocutionary acts, and 8 perlocutionary acts. Based on all the data above, it can be concluded that the most used speech act found in this data was an illocutionary act, the next was a locutionary act, and the last was a perlocutionary act.